Functional Heterogeneity of Bone Morphogenetic Protein Receptor-II Mutants Found in Patients with Primary Pulmonary Hypertension - Nishihara, Ayako (The American Society for Cell Biology, 2002)
Germline mutations in the BMPR2 gene encoding bone morphogenetic protein (BMP) type II receptor (BMPR-II) have been reported in patients with primary pulmonary hypertension (PPH), but the contribution of various types of mutations found in PPH to the pathogenesis of clinical phenotypes has not been elucidated. To determine the biological activities of these mutants, we performed functional assays testing their abilities to transduce BMP signals. We found that the reported missense mutations within the extracellular and kinase domains of BMPR-II abrogated their signal-transducing abilities. BMPR-II proteins containing mutations at the conserved cysteine residues in the extracellular and kinase domains were detected in the cytoplasm, suggesting that the loss of signaling ability of certain BMPR-II mutants is due at least in part to their altered subcellular localization. In contrast, BMPR-II mutants with truncation of the cytoplasmic tail retained the ability to transduce BMP signals. The differences in biological activities among the BMPR-II mutants observed thus suggest that additional genetic and/or environmental factors may play critical roles in the pathogenesis of PPH.